1991
DOI: 10.1128/jb.173.23.7723-7724.1991
|View full text |Cite
|
Sign up to set email alerts
|

A semiquantitative bioassay for relative virulence of Agrobacterium tumefaciens strains on Bryophyllum daigremontiana

Abstract: An assay to determine the relative virulence of wild-type and mutant strains of Agrobacterium tumefaciens on leaves of Bryophyllum daigremontiana has been developed. This assay is reproducible, is easy to learn, is not time consuming, and requires little space. The relative virulence of cellulose-minus mutants of A. tumefaciens was investigated with this assay. Some of these mutants were unaltered in virulence, while others showed a marked reduction in virulence. The wound sites were scored as positive or nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In Ag. tumefaciens, the cellulose fibrils serve to bind the bacteria tightly to the plant host cells and mutants which cannot synthesize cellulose are reduced in virulence, but still capable of infection, at least under laboratory conditions (Matthysse et al, 1981 ;Minnemeyer et al, 1991). Similarly, Smit et al (1987) showed that fibril-negative as well as fibril-overproducing mutants of R. leguminosarum showed a normal nodulation behaviour, which was confirmed for R. leguminosarum bv.…”
Section: Nodulation Assaymentioning
confidence: 95%
“…In Ag. tumefaciens, the cellulose fibrils serve to bind the bacteria tightly to the plant host cells and mutants which cannot synthesize cellulose are reduced in virulence, but still capable of infection, at least under laboratory conditions (Matthysse et al, 1981 ;Minnemeyer et al, 1991). Similarly, Smit et al (1987) showed that fibril-negative as well as fibril-overproducing mutants of R. leguminosarum showed a normal nodulation behaviour, which was confirmed for R. leguminosarum bv.…”
Section: Nodulation Assaymentioning
confidence: 95%
“…In this approach, either Kalanchoe —a nursery/house plant (8)—or carrot slices (6) are inoculated with student isolates. Use of a pathogenic strain in the infectivity assay will result in lesions, roots, or galls appearing on plant tissue in four weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Cel mutants also bind loosely to wound sites on leaves of Bryophyllum daigremontiana and can be removed by gentle water washing (Matthysse, 1983). These mutants are virulent, but are much reduced in virulence (10 to WOO-fold depending on the particular mutation) when compared to the wild type parent (Minnemeyer et al, 1991). Little is known about the genes required for the attachment of other biotypes of agrobacteria to host cells.…”
Section: Id Genetics Of Bacterial Adhesionmentioning
confidence: 97%